Sociodemographic and Perinatal Risk Factors for Autism Spectrum Disorder: A Case-control Study (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Autism spectrum disorders included impaired communication and social interaction with restricted and repetitive interests and behaviors. The rising prevalence, coupled with the severe emotional and financial impact on the families, underscores the need for a particular emphasis on the prevention of autism spectrum disorder. However, risk factors for autism have not been well studied in Bangladesh. To describe the sociodemographic and perinatal aspects of a group of Bangladeshi autistic children in order to determine its possible risk factors.This case-control study was conducted at two specialized centers at Chattogram, Bangladesh, from January 2017 to December 2017. We selected 100 autistic children aged more than three years as cases and 100 age, sex-matched children without autism as control for the study. Sociodemographic and perinatal data were collected by direct interviewing of the parents of the children and reviewing the available records. We found higher maternal education and higher maternal age (≥35 years) at birth among autistic children in comparison to the controls (18% and 17% vs. 3% and 6% respectively). Higher paternal age (≥35 years) at birth and monthly family income ≥40000 Taka were found in 26% and 42% of autistic children than 23% and 7% in the control group. Perinatal asphyxia , preterm delivery, low birth weight, and gestational diabetes mellitus were associated with an increased risk of autism. Monthly family income, prematurity, and perinatal asphyxia were independent predictive factors as derived by logistic regression analysis. Higher socioeconomic status, prematurity, and perinatal asphyxia were found to be posing a significant risk to the development of autism.Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):63-69